2010
DOI: 10.1016/j.mcn.2010.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory glia enhance neonatal axon regeneration

Abstract: Olfactory ensheathing cells (OECs) migrate with olfactory axons that extend from the nasal epithelium into the olfactory bulb. Unlike other glia, OECs are thought to migrate ahead of growing axons instead of following defined axonal paths. However it remains unknown how the presence of axons and OECs influences the growth and migration of each other during regeneration. We have developed a regeneration model in neonatal mice to examine whether (i) the presence of OECs ahead of olfactory axons affects axonal gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
86
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 63 publications
(89 citation statements)
references
References 44 publications
3
86
0
Order By: Relevance
“…The OECs are thought to promote axon growth by providing a cellular substrate containing molecules that facilitate axonal adhesion and extension and by expressing growth-promoting agents such as brain-derived neurotrophic factor, glia-derived nexin and nerve growth factor [16,17,18,19,20,21]. Indeed, OECs always extend processes ahead of the pioneer olfactory axons they ensheathe, and thus it would appear that the growth of olfactory axons is reliant on the OECs [22,23,24]. This is in contrast to Schwann cells which migrate along already defined axonal pathways during development of the peripheral nervous system [25].…”
Section: Origin Of Oecs and Population Of The Olfactory Nervementioning
confidence: 99%
See 2 more Smart Citations
“…The OECs are thought to promote axon growth by providing a cellular substrate containing molecules that facilitate axonal adhesion and extension and by expressing growth-promoting agents such as brain-derived neurotrophic factor, glia-derived nexin and nerve growth factor [16,17,18,19,20,21]. Indeed, OECs always extend processes ahead of the pioneer olfactory axons they ensheathe, and thus it would appear that the growth of olfactory axons is reliant on the OECs [22,23,24]. This is in contrast to Schwann cells which migrate along already defined axonal pathways during development of the peripheral nervous system [25].…”
Section: Origin Of Oecs and Population Of The Olfactory Nervementioning
confidence: 99%
“…Only 4 factors have been identified to functionally modulate OEC migration, 3 of which are known modulators of axonal extension (glial derived neurotrophic factor, GDNF, Nogo-66 and Slit-2) [46,47,48], and 1 extracellular matrix protein, fibulin 3 [49]. Because OECs are regarded as such important regulators of axon growth and guidance, and particularly since we have recently shown that an increased OEC migration rate leads to enhanced axon growth [22], a clear characterisation of how migration of OECs is regulated is also interesting from a clinical perspective.…”
Section: Regulation Of Oec Migration At a Molecular Levelmentioning
confidence: 99%
See 1 more Smart Citation
“…When the olfactory neuroepithelium is damaged, stem cells from the mucosa differentiate and repair it, accompanying the glial cells up to the level of the olfactory bulb. Being ensheathed by the OECs, the olfactory axons can grow and access the central nervous system; this property is not seen in axons that regenerate after injuries of the dorsal roots; they fail to enter too far into the nervous tissue of the spinal cord 10 . It was shown that adhesion molecules L1/neuron-glia cell adhesion molecule (L1/Ng-CAM) and neural cell adhesion molecule (N-CAM), both present in the plasma membranes of ensheathing cells and immature olfactory receptor neurons, help the olfactory axons to use the glial cell surfaces as a growth substratum 6 .…”
Section: The Role Of the Oecs In Olfactory Systemmentioning
confidence: 99%
“…Some of the experimental therapies pursue the reconnection of axons and neurites, for which the guided growth of axons within or along filamentous structures might be useful (1)(2)(3). Olfactory ensheathing cells (OECs) or Schwann cells (SCs) are thought to help this process, by ensheathing and guiding the growing axons (4)(5)(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%